Evaluación y diseño de un sistema de prevención de riesgos y seguridad industrial en el consorcio CV CONSTRUCCIONES - Masabanda Poaquiza, Genaro Gilberto (2015)
This research was performed using data from the CV.Construcciones consortium. At company level occupational risks are a serious problem, because there have been several accidents involving the company's economy and physical integrity of all workers producing disability and sometimes even death. The present research work is to reduce the presence of risks, incidents, accidents and hazards turn or remove them. For this the respective inspections and risk identification was conducted, in which highlight the risks and dangers that arise and affect inside the building, because job security and defense in the human element are attached by different laws than the state at the service of the worker as a means of preventing accidents. This research proposes to identify and evaluate occupational hazards in the work of construction of the housing complex Amazon and design a system of Industrial Security on the same will be flattened in each of the areas with the aim of reducing accidents at work providing security and comfort to the people working in the construction area.